Pemanfaatan Artificial Intelligence (AI) untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam - M. Arif Sofian; Ani Suraya; Alex Mufid Zamzami (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of digital technology has brought significant changes to the field of education, including Islamic Religious Education (IRE) learning. One of the technologies that has experienced substantial growth is Artificial Intelligence (AI). This study aims to examine the utilization of AI in enhancing students’ critical thinking skills in Islamic Religious Education subjects. The research employed a qualitative approach through a literature review of various journals, scientific articles, and other credible sources related to AI and IRE learning. The findings indicate that the use of AI can assist students in understanding learning materials more interactively, while also improving their analytical abilities, problem-solving skills, and critical thinking competencies. Furthermore, AI provides teachers with greater flexibility in delivering learning materials through innovative instructional methods. Nevertheless, the implementation of AI requires proper supervision to prevent students from becoming overly dependent on technology and to ensure that they continue to develop independent thinking skills. Therefore, the integration of AI in Islamic Religious Education can serve as an effective educational innovation for fostering students’ critical thinking abilities